A Descriptive Study On Teacher-Student Interaction In Speaking Class At The Seventh Year Of SMP Negeri 3 Kesesi Pekalongan In 2011/2012 Academic Year - Indriyaningsih, Karlina (2012)
The subject of this descriptive research is the seventh year of SMP Negeri 3 Kesesi Pekalongan in 2011/2012 academic year. The objectives of this research are: (1) to identify the teacher-students interaction in the speaking class at the seventh year of SMP N 3 Kesesi Pekalongan, and (2) to identify the problems occur in speaking class at the seventh year of SMP N 3 Kesesi Pekalongan. The writer uses descriptive qualitative research. The writer gets the data of this research from event, informant, and document. The events in this research are all of the activities occurred in the speaking class. Informants are the English teacher and the students of seventh year of SMP Negeri 3 Kesesi Pekalongan. Documents are all of the written information related to the interaction in speaking class. The method of collecting data is observation, interview, and data analysis of interaction in speaking class. After analyzing data, the researcher finds that (1) the teacher-students interaction in speaking class is good. The teacher implemented three steps of teaching cycle, namely Opening, Core Learning, and Closing that can be elaborated into BKOF, MOT, JCOT, and ICOT. The language uses in speaking class are teacher's modifying language, teacher's question, feedback, learners' language use in the classroom. Based on the Brown's interaction analysis system, there are five categories of the teacher-students' interaction happened in speaking class. (2) the problems faced by the students are students get difficulty in keywords, grammar mastery and pronunciation.